MAL PELAYANAN PUBLIK DI KABUPATEN MELAWI - Saiman, Defcris Yaldiso; Nurhamsyah, Muhammad; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
Public services play a strategic role in supporting effective and accountable governance. However, the quality of public services in Indonesia still faces various challenges, such as low service standards, limited supporting facilities, and the absence of an integrated service hub. Melawi Regency, as a relatively new autonomous region in West Kalimantan Province, also experiences similar conditions, where no integrated service center is yet available despite the increasing demand for public services. This situation has led to low public satisfaction with basic services and decreased bureaucratic efficiency. To address these challenges, the Melawi Regency Government has planned the development of a Public Service Mall (Mal Pelayanan Publik/MPP) as a solution to integrate cross-sectoral services within a single complex. The design process of the MPP was carried out through a rational approach that includes needs analysis, policy studies, and space program formulation based on the principles of integration and efficiency. The design concept emphasizes accessibility, social interaction, connectivity, and user comfort as the main criteria of the placemaking approach, while also considering local identity by adopting the traditional architectural form of the Dayak’s Rumah Betang. The implementation of this MPP is in line with national policy directions on public service reform based on community needs and the principles of good governance, and it is expected to improve service quality, accelerate bureaucratic processes, and strengthen public trust in local government.